Long-term effects on humoral immunity among workers exposed to 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD). Issue 6 (22nd November 2010) - Saberi Hosnijeh, Fatemeh; Boers, Daisy; Portengen, Lützen; Bueno-de-Mesquita, H Bas; Heederik, Dick; Vermeulen, Roel
Abstract : Objectives: Epidemiological studies have shown inconsistent effects on immunological parameters in subjects exposed to 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD). In this study we investigated changes in humoral immunity and prevalence of atopic diseases among workers from a Dutch historical cohort occupationally exposed to chlorophenoxy herbicides and contaminants including TCDD. Methods: 45 workers who had been exposed to high levels of TCDD in the past and 108 non-exposed workers (39 from the same factory as the exposed subjects (internal control group) and 69 from a comparable factory but without TCDD exposure (external control group)) were included in the study. Blood immunoglobulin (Ig) and complement factor (C) concentrations and specific IgE antibodies to a panel of common allergens were measured using quantitative nephelometry or ELISA. TCDD plasma levels were measured and back-extrapolated to the time of last exposure (TCDDmax) using a one-compartment first order kinetic model. Results: A borderline significant negative association between both current and predicted TCDD levels and C4 was found in multivariate analyses (β=−0.020; 95% CI=−0.040–0.010 and β=−0.020; 95% CI=−0.030–0.00, respectively). History of eczema was significantly associated with current TCDD levels in both crude (OR=1.5; 95% CI=1.03−2.2) and adjusted models (OR=1.7; 95% CI=1.08−2.7). Conclusions: Our results do not support an association between TCDD exposure and markers of humoral immunity except possibly C4. Interestingly, decreased levels of C4 have been linked to lymphoma risk, which provides some support to the putative link between TCDD and non-Hodgkin lymphoma.